Fast rejuvenation in bulk metallic glass induced by ultrasonic vibration precompression. (March 2020) - Lou, Yan; Liu, Xiao; Yang, Xiaole; Ge, Yang; Zhao, Dandan; Wang, Hao; Zhang, Lai-Chang; Liu, Zhiyuan
Abstract: Tuning energy state of metastable bulk metallic glasses (BMGs) is well known significant for understanding their glass nature and controlling their performances. Using a newly developed ultrasonic vibration precompression (UVPC) method, fast rejuvenation is achieved in a Zr-based BMG in seconds. The rejuvenated BMG has more heterogeneous structure and largely improved plasticity. The underlying mechanism is revealed. During UVPC treatment, high frequency strain energy is converted into thermal/internal energy due to heterogeneous atomic packing structure of BMG. The combined effect, resulting from external applied elastic stress, internal converted heat and ultrasonic resonance of atoms, drives the loosely packed atoms to a higher energy basin and simultaneously introduces more free volumes in the structure of the BMG. Therefore, the UVPCed BMG has more stored energy and more flow units to initiate shear bands. The findings in this work provide an effective method to modulate the energy state of BMGs and shed insights into comprehensive understanding of energy-structure-properties relationship of amorphous materials. Highlights: In this study, a novel fast rejuvenation method ultrasonic vibration precompression (UVPC) is proposed to rejuvenate BMG. Under effects of stress, heat and ultrasonic resonance, atoms of the BMG are driven to higher energy state during UVPC. Rejuvenated BMG has more heterogeneous structure, therefore plasticity is greatly improved after UVPC.